1998
DOI: 10.1126/science.281.5376.533
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Chemical Libraries, Structure, and Genomics in the Search for Kinase Inhibitors

Abstract: Selective protein kinase inhibitors were developed on the basis of the unexpected binding mode of 2,6,9-trisubstituted purines to the adenosine triphosphate-binding site of the human cyclin-dependent kinase 2 (CDK2). By iterating chemical library synthesis and biological screening, potent inhibitors of the human CDK2-cyclin A kinase complex and of Saccharomyces cerevisiae Cdc28p were identified. The structural basis for the binding affinity and selectivity was determined by analysis of a three-dimensional crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
539
1
11

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 776 publications
(569 citation statements)
references
References 28 publications
18
539
1
11
Order By: Relevance
“…5) and in the MCF-7 cells (data not shown). As cdk4 is not efficiently inhibited by purvalanol A in cell-free conditions (EC 50 850 nM), 17 these observations suggest that this compound interfered with the activation of the cdk4/cyclin D1 complex. A possible mechanism could rely on an increase of the expression of a cdki protein.…”
Section: Purvalanol a Selectively Inhibits The Phosphorylation Of Celmentioning
confidence: 78%
See 1 more Smart Citation
“…5) and in the MCF-7 cells (data not shown). As cdk4 is not efficiently inhibited by purvalanol A in cell-free conditions (EC 50 850 nM), 17 these observations suggest that this compound interfered with the activation of the cdk4/cyclin D1 complex. A possible mechanism could rely on an increase of the expression of a cdki protein.…”
Section: Purvalanol a Selectively Inhibits The Phosphorylation Of Celmentioning
confidence: 78%
“…16,17 This compound showed virtually no effect with the numerous non-cdk protein kinases tested, and had little overall effect on the contents of most cellular mRNAs. Our preliminary experiments indicated that it was active in several established cell lines at moderate concentrations (10 M), in contrast with other cdk inhibitors (olomoucine, roscovitine, butyrolactone).…”
mentioning
confidence: 99%
“…Therefore, targeting cdk activity has become an attractive strategy in cancer therapy, as it could potentially create a rationally designed inhibitor of a specific process that leads a cell to malignant transformation. To date, several families of chemical inhibitors targeted against different cdk activities have been described (Losiewicz et al, 1994;Gray et al, 1998) and, for some of them, their anticancer therapeutic potential has been demonstrated in preclinical studies (Dai and Grant, 2004). Recent attention has been focused on biological molecules, rather than chemotherapeutic agents, that combine the effectiveness of arresting cellular growth through interaction with important cell cycle checkpoint regulators, and the low risk of unexpected adverse reactions, thus improving clinical safety and patient tolerability.…”
Section: Discussionmentioning
confidence: 99%
“…The most important CDK2 / purvanalol A-simulated close contacts involve residues Ile10, Gly11, Gly13, Ala31, Val64, Phe80, Glu81, Phe82, Leu83, His84, Gln85, Asp86, Lys89, Asn132, Leu134, Ala144, Asp145, HOH5, and HOH96 while, in a similar way, CDK2-actives-simulated close contacts involve residue Ile10, Gly11, Val18, Ala31, Val64, Phe80, Glu81, Phe82, Leu83, His84, Gln85, Leu134, HOH5, and HOH96. As can be seen in Fig.5, according to literature data [6], purvanalol A forms a complete triplet of hydrogen bonds between the N7-imidazole nitrogen and the backbone nitrogen of Leu83 (distance = 2.20 ), the N6-amino group and the backbone oxygen of Leu83 (distance = 2.42 ), and the acidic C8 atom of the purine ring and the backbone oxygen of Glu81 (distance = 2.72 ). Compound 9m, forms only a pair of bidentate hydrogen bonds between the N2-indazole nitrogen and the backbone nitrogen of Leu83 (distance = 2.17 ) and N1 indazole nitrogen and the backbone oxygen of Glu81 (distance = 2.45 ); the same intermolecular hydrogen bonds of 9m were observed for all the other most active N-(indazolyl)benzamides 9e, f, i, l, n.…”
Section: Discussionmentioning
confidence: 69%
“…In particular, olomoucine 1 [4], roscovitine 2 [5], purvalanol A 3 [6], O 6 -cyclohexylmethylguanine (NU2058) 4, and its analoge NU61025 [7] are significant examples of such kind of molecules ( Fig. 1).…”
mentioning
confidence: 99%